Exploring Pre-Service Teacher Motivation: Variations Across Programs and Gender Differences in Indonesia - Budiman, Indra; Yanto, Elih Sutisna (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study examines pre-service teachers’ attitudes toward the teaching profession in Indonesia and explores how sociocultural factors shape their motivation. A mixed methods design combined a Teacher Attitude Inventory (TAI) survey (N = 460) with semi-structured interviews (n = 20). Group differences were assessed non-parametrically; interviews were then thematically analyzed to explain the quantitative patterns. Attitudes were broadly positive and stable, with no statistically significant differences by gender, program of study, or semester. Interviews revealed three interlocking strands shaping career decisions: intrinsic–altruistic commitment (meaning, contribution), pragmatic–extrinsic calculus (stability, compensation, entry routes), and sociocultural positioning (family expectations, gendered identities, perceived status). These strands clarify why professional pride and learner-centred beliefs coexist with cautious views of career prospects and perceived limits on teacher voice. Results support (i) gender sensitive mentorship, (ii) discipline-specific motivational scaffolds in ITE, (iii) recruitment and bonded scholarship schemes for rural deployment, and (iv) well-being supports that enhance agency and retention. By integrating group-level convergence with culturally situated narratives, the study reframes motivation as a contextual phenomenon and offers actionable levers for teacher workforce policy and ITE program design.